The effects of economic crisis to logistics outsourcing - Dimitrios Folinas; Dimitrios Aidonis (International Journal of Business Science & Applied Management (IJBSAM), 2012)
The aim of this paper is the investigation of the effects that the economic crisis has on the logistics services sector in Greece. It presents and analyses the findings of a research, which, via a questionnaire, asked managers at the examined sector first to identify the effects and second the practices and approaches that the managers suggested to confront with these effects. The findings of the research revealed that the logistics' service providers have been significantly affected by the crisis and these effects have influenced all the main functional areas of the logistics management (procurement, warehousing, inventory management, transportation and distribution). Moreover, they are not optimistic about the future as they believe that the sector will be significantly decreased in the next few years and the competition will be increased. Performance measurement and optimization of their logistics' processes and functions and the decrease of the operation costs are considered to be their weapons to this battle. This research can be considered as a pilot study, as the Greek economy has been seriously affected during the global financial crisis. Worldwide, 3pl companies can use the findings of this study in order to overcome potential difficulties that might face in near future.
Keywords: 650; logistics; outsourcing; 3PL's; economic crisis; Greece